EDUKASI PERENCANAAN KEUANGAN DAN INVESTASI PADA GENERASI Z DI WILAYAH CAWANG JAKARTA TIMUR (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Abstract: According to BPS - Statistics Indonesia in 2020 that the current population of Indonesia are dominated by Generation Z called i-Generation or the internet generation who had consumerism attitudes, impulse buying, had no understanding of the products, monetary risks and unwilling to invest. The objective of this activity is to aims to provide an understanding Z Generation of financial planning and investment, learn how to manage money in area such as investments, for both personal and business purposes, as well as understanding Legitimate Financial Institutions. This activity targeting Generation Z as a primary audience and 50 young people are selected as audience from Cawang area, East Jakarta and nearest Cawang. We do a pre-test and post-test system, this helped us to compare the condition before and after training, with hope audience can experience improved. As a result, there is a tendency for young people experienced improved about finance and investments. Keywords: education, gen z, investments